The effect of HLA genotype on disease onset and severity in CTLA-4 insufficiency - Posadas-Cantera, Sara; Mitsuiki, Noriko; Emmerich, Florian; Patiño, Virginia; Lorenz, Hanns-Martin; Neth, Olaf; Dybedal, Ingunn; Taskén, Kjetil; Schäffer, Alejandro A.; Grimbacher, Bodo; Gámez-Díaz, Laura (Frontiers in Immunology, 2025)
Human Cytotoxic-T-lymphocyte-antigen-4 (CTLA-4) insufficiency caused by heterozygous germline mutations in CTLA4 is a complex immune dysregulation and immunodeficiency syndrome presenting with reduced penetrance and variable disease expressivity, suggesting the presence of disease modifiers that trigger the disease onset and severity. Multiple genetic and non-genetic potential triggers have been analyzed in CTLA-4 insufficiency cohorts, however, none of them have revealed a clear association to the disease. Multiple HLA haplotypes have been positively or negatively associated with various autoimmune diseases and inborn errors of immunity (IEI) due to the relevance of MHC in the strength of the T cell responses. In this exploratory study, we investigated the association of disease onset, severity and clinical manifestations of CTLA-4 insufficiency with specific HLA class I (A, B and C) and class II (DRB1 and DQB1) alleles in forty-three individuals harboring heterozygous mutations in CTLA4. Twenty-six out of the 43 recruited individuals presented moderate or severe clinical symptoms whereas 17 were completely healthy. HLA frequency analysis, odds ratio analysis and genetic linkage analysis showed no positive association between the HLA genotypes analyzed with the disease onset or the disease severity. However, we found potential risk associations of HLA-DQB1*05:01 and HLA-DRB1*01:02 with respiratory tract involvement and HLA-C*05:01 with affection of the neurological system in the CTLA-4-insufficient patients. Additionally, we found a potential protective association of HLA-DRB1*01:01 with gastrointestinal symptoms. Thus, we advocate for further investigation of specific class I and class II HLA alleles as potential disease modifiers in larger clinical cohorts of CTLA-4 insufficiency.CHAI CTLA-4 haploinsufficiency CVID common variable immunodeficiency CTLA-4 cytotoxic T-lymphocyte antigen 4 EBV Epstein Barr virus HLA human leukocyte antigen IEI inborn errors of immunity LOD logarithm of odds MHC major histocompatibility complex OR odds ratio TCR T-cell receptor 1